Three-dimensional of lingual arch form and creation of templates in Iraqi normal occlusion - Ali Jamal Abdul Razzaq; Zaid Dewachi (Wolters Kluwer Medknow Publications, 2023)
OBJECTIVES: To evaluate the lingual dental arch form types in class I canine and molar relationship based on scanning dental cast models using three-dimensional laser scan and to give a new lingual arch form pattern created on this classification to be used for clinical submission by studying three-dimensional virtual models of the normal occlusion samples. MATERIALS AND METHODS: Maxillary and mandibular casts of 120 young adults (18-24 ± 1.84 years) have normal occlusion that was scanned using a 3Shape E1 laser scanner, and then, the data were analyzed using SPSS software; then, we used K-means cluster to classify the arch form into clusters depending on the measurement of 10 landmarks designated on the lingual surface of the teeth. RESULTS: Many dental arch patterns have been established for both the mandible and the maxilla. CONCLUSION: The minimum sizes were found in the females, and the biggest sizes were found in the male subjects, and three sets were well defined for each sex; three categories for each mandible and maxilla are as follows: narrow, mid, and broad. The lingual arch form can be classified into three groups based on posterior and anterior dimensions, so a template of the three arch forms has been exemplified.